Green Product, Green Marketing, and Green Brand Image on Customer Loyalty in Sustainable Banking: The Moderating Role of Customer Satisfaction - Khadijah Ritonga; Muhammad Iqbal Fasa (Talent: Journal of Economics and Business, 2026)
The increasing pressure for environmental sustainability has encouraged the banking industry to adopt more responsible and sustainable business practices. This study aims to examine the influence of green product, green marketing, and green brand image on customer loyalty in sustainable banking, with customer satisfaction as a moderating variable. Using a Systematic Literature Review (SLR) approach, this study analyzes 26 international articles published between 2021 and 2025. The findings indicate that green product, green marketing, and green brand image consistently have a positive contribution to customer loyalty. In addition, customer satisfaction strengthens these relationships by enhancing customers’ positive evaluations and long-term commitment to sustainable banking services. This study provides strategic implications for Islamic and conventional banking institutions in integrating sustainability into marketing, branding, and service strategies to build stronger customer loyalty.